Alterations of Striatal Subregions in a Prion Protein Gene V180I Mutation Carrier Presented as Frontotemporal Dementia With Parkinsonism - Chen, Zhongyun; Ma, Jinghong; Liu, Li; Liu, Shuying; Zhang, Jing; Chu, Min; Wang, Zhen; Chan, Piu; Wu, Liyong (Frontiers in Aging Neuroscience, 2022)
Objective: To explore the roles of striatal subdivisions in the pathogenesis of frontotemporal dementia with parkinsonism(FTDP) in a patient resulting from prion protein gene (PRNP) mutation. Methods: This patient received clinical interviews and underwent neuropsychological assessments, genetic testing, [18F]-FDG PET/MRI, and [18F]-DTBZ PET/CT. Region of interest analysis was conducted concerning metabolism, and dopamine transport function between this patient and 12 controls, focusing on the the striatum subregions according to the Oxford-GSK-Imanova Striatal Connectivity Atlas. Results: A 64-year-old man initially presented with symptoms of motor dysfunction and subsequently behavioral and personality changes. FTDP was initially suspected. Sequence analysis disclosed a valine to isoleucine at codon 180 in PRNP. Compared to controls, this patient had a severe reduction (>2SD) of standard uptake value ratio (SUVR) in the limbic subregion and executive subregion but relative retention of metabolism in rostral motor and caudal motor subregion using [18F]-FDG PET/MRI, and the SUVR decreased significantly across the striatal in [18F]-DTBZ PET/CT, especially in the rostral motor and caudal motor subregions. Conclusion: The alteration of frontal striatal loops are involved in cognitive impairment in FTDP and the development of parkinsonism in FTDP may be primarily due to the involvement of the presynaptic nigrostriatal loops rather than degeneration of motor areas in PRNP V180I mutation.